Application of cooperative learning in teaching English among school teachers in the Kuala Selangor school district / Sarimah Abdul Rahim - Abdul Rahim, Sarimah (2010)
Extensive researches around the world validate cooperative learning effectiveness as an instructional method in teaching. Not only it is able to improve academic achievement but it also provides a conducive environment which promotes active learning and interaction among students and this serves as a platform to develop good social skills. Cooperative learning should become a common instructional method in Malaysian classfboms, since the current Malaysian teaching philosophy advocates a more student-centred teaching practices compared to the previous curriculum which rely heavily on traditional teacher-centred teaching approach. These factors and the limited number of studies which focus on the teachers as practitioners of cooperative learning in second language learning environment in Malaysia have prompted this study to be carried out. Subsequently, the objectives of this study were to examine English teachers' and their current cooperative learning in the teaching of English, their perceptions in using the method in class and the motivational variables that affect the application of cooperative learning. Samples were taken from five selected secondary schools in the district of Kuala Selangor, Selangor. The data were elicited through questionnaires which were distributed to 55 English teachers in the schools and interviews with five teachers who were selected at random. The findings showed that eighty percent of the respondents were practitioners of cooperative learning and they were generally positive in integrating cooperative learning in teaching and have an adequate grasp of the approach. However, the other twenty percent of the teachers were not keen in applying the method in their teaching by citing reasons such as lack of support from the school management and lack of confidence. The study also discovered that in relation to motivational variables, the teachers perceived value of cooperative learning play a role in their decision in becoming a practitioner or a non-practitioner of the method. It is recommended that in-service and trainee teachers are given a more intensive course on cooperative learning so that they would have a good understanding of its principles and benefits to increase both their confidence level in using the method as well as their perceived value on the method in the effort to encourage them to adopt it in the teaching and learning of English.